Chaotic Tax Regulations in Indonesia - Hartanto, Yohanes (Advances In Social Humanities Research, 2025)
Recently, the Government together with the House of Representatives or the Government alone often issue laws and regulations that are "sweeping the universe" or using the "Omnibus Law" method, which means that according to article 64 paragraph 1b of Law No. 13 of 2022, one regulation can change or even repeal many similar rules and which have the same hierarchy, this method is applied to the formation of laws and ministerial regulations, including the Regulation of the Minister of Finance, but because the regulation of the nature of the "Omnimbus Law" usually consists of very many articles related to other regulations, many chapters and pages, then if in the process of formation it is not careful and with the right socialization to the public it can result in the potential for writing errors as a result there will be a discrepancy between the content of the regulation and the purpose of forming the regulation, so that it can cause legal uncertainty, "misperception", differences of belief or debate between stakeholders at the level of regulatory implementation and can even become a dispute or "dispute" in the Court, in the event that it occurs in the Tax Regulation, the dispute will be resolved through the Tax Court.